Immunotherapy-induced autoimmune hypophysitis - Valecha, Gautam; Pant, Manisha; Ibrahim, Uroosa; Atallah, Jean P (Journal of oncology pharmacy practice, 2019)
Autoimmune hypophysitis is an immune-related adverse event of immune checkpoint inhibitors. In this article, we present the case of a 58-year-old female patient who presented to the emergency room with gradually worsening nonspecific symptoms of headache, nausea, vomiting and decreased oral intake of one week duration. The patient had been diagnosed with relapsed extensive stage small cell lung cancer. She was being treated with a combination of ipilimumab and nivolumab after progression on chemotherapy. Gadolinium-enhanced magnetic resonance imaging of head revealed pituitary enlargement up to 1.5 cm and pituitary stalk enlargement up to 4 mm consistent with hypophysitis. The patient was treated with corticosteroids resulting in rapid resolution of her symptoms. The objective of our report is to highlight this rare but important adverse event associated with checkpoint inhibitors, and discuss its clinical features, diagnostic work-up and treatment.